Cytoglobin as a Prognostic Factor for Pancreatic Ductal Adenocarcinoma: A Retrospective Analysis of 75 Patients. Issue 7 (11th August 2021) - Kono, Hiroshi; Hosomura, Naohiro; Amemiya, Hidetake; Kawaida, Hiromichi; Furuya, Shinji; Akaike, Hidenori; Kawaguchi, Yoshihiko; Sudo, Makoto; Ichikawa, Daisuke
Abstract : Objectives: The aim was to evaluate the relationship between cytoglobin (Cygb) expression and both clinicopathologic factors and prognosis in patients with pancreatic ductal adenocarcinoma (PDAC). Methods: Seventy-five patients with PDAC who underwent pancreatectomy between 2009 and 2014 at our department were included. Diagnosis was based on World Health Organization standards, with staging by TNM classification of Union for International Cancer Control. Expressions of Cygb, phosphoinositide-3 kinase, phosphorylated protein kinase B, interleukin-6, and vascular endothelial growth factor were evaluated by immunohistochemical staining of resected surgical specimens and densitometrical analysis. Results: Elevated expression of Cygb was found mainly in carcinoma cells of PDAC. Patients with low expression of Cygb showed significantly shorter disease-free survival and disease-specific survival than those with high expression. There was also a significant negative correlation between Cygb expression and the expressions of phosphoinositide 3-kinase, phosphorylated protein kinase B, interleukin-6, and vascular endothelial growth factor. In univariate analysis, Cygb expression, clinical stage, histologic tumor grade, lymphatic invasion, and vascular invasion were prognostic factors. In multivariate analysis, Cygb expression and the clinical stage were independent prognostic factors. Conclusions: Loss of Cygb may contribute to tumor recurrence and poor prognosis of PDAC by increases in angiogenic factor.